Sharia Finance, SDGs, and Economic Growth: Empirical Evidence from Muslim Countries in Asia - Nisa Azzahro; Muthoifin; Shahbaz Alam (Profetika: Jurnal Studi Islam, 2024)
Objective: This study examines the role of Sharia finance in driving economic growth and supporting the achievement of the SDGs in Muslim countries in Asia. The main objective is to analyze the development, challenges, and contributions of Sharia financing systems, as well as to compare their performance with conventional financial systems in promoting economic growth, financial inclusion, and sustainability. Theoretical framework: The theoretical framework is grounded in Islamic financial principles that prohibit riba (usury), gharar (excessive uncertainty), and investment in haram sectors, while emphasizing social justice, risk-sharing, ethical investment, and inclusive development, which are closely aligned with the core objectives of the SDGs, particularly SDG 1, SDG 8, and SDG 10. Literature review: The literature review synthesizes previous studies on the development of Islamic finance in Malaysia, Indonesia, Brunei Darussalam, and Muslim regions of the Philippines, focusing on regulatory frameworks, levels of Islamic financial literacy, product innovation, and the sector’s contribution to regional economic growth and sustainable development. Methods: Methodologically, this study employs a descriptive and comparative literature-based approach, analyzing the implementation and evolution of Sharia and conventional financial systems across selected Asian Muslim countries, while identifying key challenges and opportunities in advancing SDG-oriented finance. Results: The findings reveal that Sharia finance has experienced significant growth in Asia, with Malaysia emerging as a global Islamic finance hub and Indonesia demonstrating substantial market potential. Despite this progress, challenges remain, including limited financial literacy, regulatory fragmentation, and the need for greater product and technological innovation. Empirical evidence suggests that Sharia finance contributes positively to financial inclusion, sustainable economic growth, financial stability, human capital development, and technological adoption, thereby reinforcing its relevance to SDG-driven development strategies. Implications: The study’s implications highlight the importance of strengthening Islamic financial literacy, harmonizing regulations, and encouraging innovation to position Sharia finance as a strategic pillar of sustainable and inclusive economic growth in Asia. Novelty: The novelty of this research lies in its comprehensive and integrative analysis of Sharia finance within an SDG framework, demonstrating its comparative advantages over conventional finance in fostering equitable and sustainable development.